Cytoglobin Silencing Promotes Melanoma Malignancy but Sensitizes for Ferroptosis and Pyroptosis Therapy Response - Joey De Backer; Darko Maric; Karim Zuhra; Annemie Bogaerts; Csaba Szabo; Wim Vanden Berghe; David Hoogewijs (Antioxidants, 2022)
Despite recent advances in melanoma treatment, there are still patients that either do not respond or develop resistance. This unresponsiveness and/or acquired resistance to therapy could be explained by the fact that some melanoma cells reside in a dedifferentiated state. Interestingly, this dedifferentiated state is associated with greater sensitivity to ferroptosis, a lipid peroxidation-reliant, iron-dependent form of cell death. Cytoglobin (CYGB) is an iron hexacoordinated globin that is highly enriched in melanocytes and frequently downregulated during melanomagenesis. In this study, we investigated the potential effect of CYGB on the cellular sensitivity towards (1S, 3R)-RAS-selective lethal small molecule (RSL3)-mediated ferroptosis in the G361 melanoma cells with abundant endogenous expression. Our findings show that an increased basal ROS level and higher degree of lipid peroxidation upon RSL3 treatment contribute to the increased sensitivity of CYGB knockdown G361 cells to ferroptosis. Furthermore, transcriptome analysis demonstrates the enrichment of multiple cancer malignancy pathways upon CYGB knockdown, supporting a tumor-suppressive role for CYGB. Remarkably, CYGB knockdown also triggers activation of the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome and subsequent induction of pyroptosis target genes. Altogether, we show that silencing of CYGB expression modulates cancer therapy sensitivity via regulation of ferroptosis and pyroptosis cell death signaling pathways.